(untitled) (Gaceta Técnica, 2023)
There are numerous tools for structural calculation that allow simplifying processes through graphical interfaces; however, currently there is no commercial software that allows the design of Kaiser Bolted Bracket prequalified connections. Therefore, the fundamental objective of this research is to develop a program that allows the design of this type of connections, called KAISER CONNEX, created using the MATLAB App Designer tool version R2020a. This program facilitates the design of the prequalified connection according to the specifications of the ANSI/AISC 358-16 Standard. KAISER CONNEX has a dynamic and easy-to-use interface, it allows the user to generate a detailed report of the designed connection, providing a summary of the analysis carried out with the ability to view and export the different views to different image formats according to the geometry of the connection entered